Asset Management Public Assessment of Road Infrastructure - Golgota, Alma; Bardh, Diana (European Journal of Multidisciplinary Studies, 2016)
For several years, the Albanian Road Authority under the administration of the Ministry of Infrastructure also public transport, following the process of maintenance of national roads, even the Albanian Fund for Development of road infrastructure management agency that handled the funds public for the construction of national infrastructure in rural areas, have seen the need to develop a strategy for the management of maintenance and financial management, based on current accounting principles and efficiency in the use of funds for investment. This includes the use of a balance of investments made to launch a database for years and the development of basic documents for the planning and control of public spending in these activities. The question that arises and requires an analysis is